Porosity problems: Comparing and reviewing methods for estimating porosity and volume of wood jams in the field. Issue 13 (18th August 2020) - Livers, Bridget; Lininger, Katherine B.; Kramer, Natalie; Sendrowski, Alicia
Abstract: Porosity, or void space, of large wood jams in stream systems has implications for estimating wood volumes and carbon storage, the impacts of jams on geomorphic and ecological processes, and instream habitat. Estimating porosity and jam dimensions (i.e. jam volume) in the field is a common method of measuring wood volume in jams. However, very few studies explicitly address the porosity values in jams, how porosity is calculated and assessed for accuracy, and the effect such estimates have on carbon and wood budgets in river corridors. We compare methods to estimate jam porosity and wood volume using field data from four different depositional environments in North America (jam types include small in‐channel jams, large channel‐margin jams, a large island apex jam, and a large coastal jam), and compare the results with previous studies. We find that visual estimates remain the most time‐efficient method for porosity estimation in the field, although they appear to underpredict back‐calculated porosity values; the accuracy of jam porosity, and thus wood volume, estimates are difficult to definitively measure. We also find that porosity appears to be scale invariant, dictated mostly by jam type, (which is influenced by depositional processes), rather than the size of the jam. Wood piece sorting and structural organization are likely the most influential properties on jam porosity, and these factors vary according to depositional environment. We provide a framework and conceptual model that uses these factors to demonstrate how modeled jam porosity values differ and give recommendations as a catalyst for future work on porosity of wood jams. We conclude that jam type and size and/or the study goals may dictate which porosity method is the most appropriate, and we call for greater transparency and reporting of porosity methods in future studies. © 2020 John Wiley & Sons, Ltd. Abstract : Porosity of wood jams in streams has implications for estimating wood volumes and impacts of jams on geomorphic and ecological processes. We compare methods to estimate jam porosity and wood volume using field data in North America. Accuracy of porosity estimates is still unknown, but visual estimates, although likely underestimated, remain the most time‐efficient method. We provide a framework that uses wood piece sorting and structural organization with modeled jam porosity values and methodological recommendations for future studies.